Sex-related differences in long-term outcome of heart failure in low-risk patients with atrial fibrillation. A Swedish registry case-control study. (3rd October 2022) - Basic, C; Hansson, P O; Zverkova Sandstrom, T; Johansson, B; Fu, M; Mandalenakis, Z
Abstract: Background: Knowledge about sex-related differences regarding long-term risk of heart failure (HF) among patients with atrial fibrillation (AF) is limited. Aim: To evaluate the impact of sex on risks for new onset HF in patients with AF. Methods: All patients from the Swedish National Patient Register, with a first-time diagnosis of AF between 1987 and 2018 were identified and compared with two matched controls without AF from the Total Population Register. Patients <18 years, or any previous cardiovascular disease, diabetes mellitus and renal failure at the baseline were excluded. Results: In total 227, 811 patients and 452, 712 controls were included; 44.5% were women. The mean age (SD) for men was 65.5 (15) vs. 72.7 (13) in women (p<0.0001). The incidence rate for HF onset per 1000 person-years within one and five years after AF diagnosis was 77.3 (75.5–79.1) and 45.0 (44.3–45.7) in women vs. 66.5 (65.0–68.0) and 35.3 (34.8–35.9) in men, respectively. The incidence rate for HF onset increased with age in both patients with AF and controls, but was generally more pronounced in women. Women had 26% and 34% higher risk for HF onset, within five and thirty years, respectively. The highest risk for HF onset was found in women 18–34 years and 35–49 years of age, HR 24.64 (95%, confidence interval (CI) 7.59–80.0) and 8.09 (95%, CI 6.34–10.33) vs. 9.86 (95%, CI 6.81–14.27) and 6.52 (95%, CI 5.87–7.25) in equally old men. The mortality rate after HF was 42.3% and 33.1% in women and men with AF (p<0.0001). Conclusion: In this nationwide, register-based cohort study, when compared to matched controls we found that the risk for HF onset was higher in women with AF, particularly in reproductive age, highlighting great importance of further research for prevention of HF in young women with AF but without any other cardiovascular risk factors. Funding Acknowledgement: Type of funding sources: None.